FORMULATION DEVELOPMENT AND EVALUATION OF CHRONOMODULATED DRUG DELIVERY SYSTEM BY ZAFIRLUKAST - KRISHNA, N. SHIVA; JAYANTHI, B.; MADHUKAR, A. (International Journal of Applied Pharmaceutics, 2021)
Objective: The main objective of the present study was to formulate and evaluate a time-controlled single-unit oral pulsatile drug delivery system containing Zafirlukast for the prevention of nocturnal asthma attacks. To provide time-scheduled drug release for Asthma disease. It is used for preventing asthmatic attacks at early morning. Pulsatile release dosage form is increasing patient compliance by reducing the dosing frequency, especially in the early morning. Methods: Core tablets were prepared by incorporating different concentrations of natural and synthetic super disintegrants. Drug-containing core tablets (ZC1-ZC15) with different compositions of natural super disintegrants (Plantago ovata seed powder, Locust bean gum) synthetic super disintegrants (Sodium starch glycolate (SSG), Cross carmellose sodium (CCS), Crospovidone (CP)) were prepared by direct compression technique. The core tablets were subjected to pre-formulation, physicochemical and In vitro drug release studies. The fast disintegrating core tablet formulation was selected and press-coated tablets (P1-P11) were prepared with different compositions of hydrophobic polymers Eudragit RS100, Eudragit RL 100, Ethylcellulose and hydrophilic polymers Hydroxypropyl methylcellulose K4M, K100M. The optimized formulation was selected and quantified based on in vitro drug release profile in simulated gastric and intestinal fluids. Results: The pre and post-compression parameters of tablets were also found to be within limits. Formulation ZC5 with 16 mg of Locust bean gum showed the least disintegrating time, i.e., 22.13 sec, and was selected as the best immediate release core tablet. The press-coated tablet formulation P8 having 62.5 mg Eudragit RS100 and 62.5 mg of HPMC K4M in ratio 1:1 over the core tablet ZC5 showed rapid and drug release nearly after 4 h lag time and 98.86 % up to 12 h. Accelerated stability studies of the optimized formulation P8 indicated no significant difference in release profile after 3 mo. Conclusion: The in vitro dissolution study showed that lag time before drug release was highly affected by the coating amount level and nature of coating polymer used. Time-controlled pulsatile release tablets can be prepared using press-coating techniques.